Improvement of the High-Performance Al-Doped LiNi1/3Co1/3Mn1/3O2 Cathode Material for New Electro-Optical Conversion Devices - Gao, Yumei; Yuan, Wangran; Dou, Xinqi (Frontiers in Physics, 2021)
The ternary cathode material LiNi1/3Co1/3Mn1/3O2 has been extensively focused on as the power sources for new optoelectronic devices and lithium-ion batteries. To improve the electrochemical performance, Al doping is one of the effective strategies. Based on the density functional theory of first-principles, the band gap, volume, partial density of states, lithiation formation energy, electron density difference, and potential energy of electrons for Li1.0-xAlxNi1/3Co1/3Mn1/3O2 were calculated with Materials studio, Nanodcal and Matlab. Results show that Li0.9Al0.1Ni1/3Co1/3Mn1/3O2 has a better conductivity and cycling capability. The potential energy maps of Li1.0-xAlxNi1/3Co1/3Mn1/3O2 stimulated in Matlab indicate that the rate capability is promoted after Al doping due to the potential well lower. Our theoretical advice could be a great election for the studies of the power application of the new optoelectronic devices. In addition, our methods could provide some theoretical guidance for the subsequent electrochemical performance investigations on doping of lithium-ion battery materials.